The Bacterial Species Campylobacter jejuni Induce Diverse Innate Immune Responses in Human and Avian Intestinal Epithelial Cells - John, Daniel A.; Williams, Lisa K.; Kanamarlapudi, Venkateswarlu; Humphrey, Thomas J.; Wilkinson, Thomas S. (Frontiers in Microbiology, 2017)
Campylobacter remain the major cause of human gastroenteritis in the Developed World causing a significant burden to health services. Campylobacter are pathogens in humans and chickens, although differences in mechanistic understanding are incomplete, in part because phenotypic strain diversity creates inconsistent findings. Here, we took C. jejuni isolates (n=100) from multi-locus sequence typed collections to assess their pathogenic diversity, through their inflammatory, cytotoxicity, adhesion, invasion and signalling responses in a high-throughput model using avian and human intestinal epithelial cells. C. jejuni induced IL-8 and CXCLi1/2 in human and avian epithelial cells, respectively, in a MAP kinase-dependent manner. In contrast, IL-10 responses in both cell types were PI 3-kinase/Akt-dependent. C. jejuni strains showed diverse levels of invasion with high invasion dependent on MAP kinase signalling in both cell lines. C. jejuni induced diverse cytotoxic responses in both cell lines with cdt-positive isolates showing significantly higher toxicity. Blockade of endocytic pathways suggested that invasion by C. jejuni was clathrin- and dynamin-dependent but caveolae- independent in both cells. In contrast, IL-8 (and CXCLi1/2) production was dependent on clathrin, dynamin and caveolae. This study is important because of its scale, and the data produced, suggesting that avian and human epithelial cells use similar innate immune pathways where the magnitude of the response is determined by the phenotypic diversity of the Campylobacter species.